Quantitative assessment of epoxide formation in oil and mayonnaise by 1H-13C HSQC NMR spectroscopy. (1st October 2022) - Boerkamp, Vincent J.P.; Merkx, Donny W.H.; Wang, Jianli; Vincken, Jean-Paul; Hennebelle, Marie; van Duynhoven, John P.M.
Graphical abstract: Highlights: Epoxides can be quantified reproducibly and sensitively by HSQC NMR. Lipid hydroperoxides, aldehydes, and epoxides can be quantified simultaneously. Epoxides appear to be primarily formed via alkoxyl radicals. Epoxides have a limited potential as an early oxidation marker. Quantification of epoxides is critical for resolving lipid oxidation pathways. Abstract: Lipid oxidation is detrimental for the quality of oil-based foods. Historically, lipid oxidation research focussed on hydroperoxides and aldehydes, but a third class, the epoxides, have been proposed to resolve observed mechanistic anomalies. Here, we developed a 2D 1 H- 13 C HSQC NMR spectroscopic method to quantify epoxides in food in a reproducible (relative standard deviation ≤11.6 %) and sensitive (LoQ 0.62 mmol/kg oil) manner. Lipid hydroperoxides, aldehydes, and epoxides generated in rapeseed oil and mayonnaise were quantified over time by NMR. Epoxides accounted at most for 10–40 % of the products. They were formed after hydroperoxide accumulation, most likely primarily via alkoxyl radical intermediates, which limits their potential as an early oxidation marker. As 99 % and ∼60 % of the epoxide signal intensities were assigned in a fatty acid and sub-structure specific manner, respectively, our quantitative HSQC method will enable unravelling and quantitative modelling of lipid oxidation mechanisms.